Management of altered metabolic activity in Drosophila model of Huntington's disease by curcumin. - Aditi, K.; Singh, A.; Shakarad, M.N.; Agrawal, N. (Experimental biology and medicine (Maywood, N.J.), 2022)
Huntington's disease (HD) is a devastating polyglutamine disorder characterized by extensive neurodegeneration and metabolic abnormalities at systemic, cellular and intracellular levels. Metabolic alterations in HD manifest as abnormal body weight, dysregulated biomolecule levels, impaired adipocyte functions, and defective energy state which exacerbate disease progression and pose acute threat to the health of challenged individuals in form of insulin resistance, cardiovascular disease, and energy crisis. To colossally mitigate disease symptoms, we tested the efficacy of curcumin in Drosophila model of HD. Curcumin is the bioactive component of turmeric (Curcuma longa Linn), well-known for its ability to modulate metabolic activities. We found that curcumin effectively managed abnormal body weight, dysregulated lipid content, and carbohydrate level in HD flies. In addition, curcumin administration lowered elevated reactive-oxygen-species levels in adult adipose tissue of diseased flies, and improved survival and locomotor function in HD flies at advanced disease stage. Altogether, these findings clearly suggest that curcumin efficiently attenuates metabolic derangements in HD flies and can prove beneficial in alleviating the complexities associated with HD.